The Process The Formation of The Collective Leadership on The Corruption Eradication Commission - Muslimin, Muslimin; Gani, Yuli Andi; Suryadi, Suryadi; Saleh, Choirul (JPAS (Journal of Public Administration Studies), 2021)
This article was written based on the findings of research that examines the process of formation of collective leadership implemented by the Corruption Eradication Commission (Komisi Pemberantasan Korupsi: KPK) in Indonesia during its inception in 2003 until the end of the leadership of Abraham Samad 2015. The results of the study indicate that the KPK's collective leadership was gradually formed through several stages can be identified in 3 development cycles. The first stage is a pioneering cycle that requires prerequisites for the formation of collective leadership in order to operate the leadership mechanism in the KPK's organizational structure. Second, the critical cycle, namely the operational trials of collective leadership that have the opportunity to succeed or fail. This cycle is characterized by collaboration between structures in the collective decision making process. Third, the operational stabilization cycle, is a stage of development that leads to the cohesiveness of KPK members and results in superior level of performance.